Relação entre impulsividade e suícidio em pacientes com transtorno afetivo bipolar - Paulo Henrique Paiva de Moraes (2011)
Many studies have investigated the possible relationship between suicide attempts and impulsivity in patients with bipolar disorder, but their results often conflict. This absence of uniform results may be related to methodological and conceptual matters such as the difficultyin defining impulsivity. The aim of this research was to evaluate the relationship between impulsivity and suicide attempts in a sample of patients with bipolar disorder. The Iowa Gambling Task and Conners Continuous Performance Test evaluated impulsivity in 95patients with bipolar disorder (including 42 suicide attempters) and 115 control participants. A factorial analysis evaluated the adequacy of the instruments. Furthermore, a multiple regression analysis developed a model to predict suicide attempts. The final model includedonly significant variables (p < 0.05). Non-planning impulsivity and borderline personality disorder predicted suicide attempts in the final model (F = 21.205; p < 0.001; R2 = 31.6%). Our results point to a specific type of impulsivity related to making decisions, lack of planning and borderline personality disorder. This type of impulsivity is a risk factor forsuicide attempts in patients with bipolar disorder. Future studies should investigate the neurobiological mechanisms that underlie the relationships among impulsive behavior, borderline personality disorder and suicidality.